Nine years of development in establishing the journal as a learning and research hub in STEM education - Yeping Li (International Journal of STEM Education, 2023)
Abstract From August 2014 to July 2023, the International Journal of STEM Education went through nine publication cycle years. In this editorial, I provide a brief summary of the journal’s development up to and including its ninth publication cycle year (August 2022–July 2023), and share insights about the journal’s efforts in establishing itself as a worldwide learning and research hub for the broad STEM education community.